AI-Enabled Smart Education System - Mr. Ajit Anna Musale,; Mr. Kartik Gorakshnath Tanpure,; Mr. Pratham Vinod Tatte,; Prof. Khatal Kavita B., (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
AI-Enabled Smart Education System is an intelligent academic management platform designed to enhance institutional efficiency through automation, predictive analytics, and artificial intelli-gence. The system unifies students, faculty, and administrators into a single adaptive digital ecosys-tem, streamlining academic and administrative workflows. The platform incorporates an AI-powered chatbot for academic and administrative assistance, predictive analytics for performance tracking, and automated dashboards for institutional reporting and monitoring. By leveraging cloud computing, data analytics, and machine learning, the system ensures reliability, scalability, and continuous availability for users. Developed using React.js, Node.js, Dialogflow, and AWS Cloud, AI-Enabled Smart Education System integrates MySQL and MongoDB databases for secure and efficient data management. Ex-perimental analysis indicates a 40% reduction in administrative workload, 92% chatbot accuracy, and over 90% prediction precision, confirming the systems performance and reliability. This project demonstrates how artificial intelligence and cloud technology can revolutionize traditional education systems into intelligent, adaptive, and data-driven environments that foster collaboration, engage-ment, and innovation in learning and management.
Keywords: Artificial Intelligence; Educational Management System; Machine Learning; Predictive An-alytics; Chatbot; Cloud Computing; Smart Campus; Academic Automation